1961
DOI: 10.5957/jsr.1961.5.2.13
|View full text |Cite
|
Sign up to set email alerts
|

Instability of Ventilated Cavities

Abstract: Cavitation number σ is defined by σ = (p0pk)/q. It can be controlled by controlling the dynamic pressure q, the ambient pressure p0, or, in the case of quasi-steady cavities, the internal cavity pressure pk. The present investigation was undertaken to study methods of controlling pk by adding air to the wakes of fully submerged bodies. This process has been called ventilation. It was found that for small air-flow rates, pk increased and σ decreased nearly linearly with the rate of air supply. It was also found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1973
1973
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Neither scenario above favours drag reduction, since the optimal condition demands a continuous cavity or layer of gas covering the underwater surface of marine vehicles (Ceccio 2010). Silberman & Song (1961) investigated experimentally the development of the ventilation cavity in a vertical water tunnel, and revealed that a stable cavity could be produced only when the ventilation cavitation number exceeded a critical value. Using a similar experimental set-up, Vigneau et al (2001) suggested that the thickness of the boundary layer does not have any significant influence on the dynamics of the cavity.…”
Section: Introductionmentioning
confidence: 99%
“…Neither scenario above favours drag reduction, since the optimal condition demands a continuous cavity or layer of gas covering the underwater surface of marine vehicles (Ceccio 2010). Silberman & Song (1961) investigated experimentally the development of the ventilation cavity in a vertical water tunnel, and revealed that a stable cavity could be produced only when the ventilation cavitation number exceeded a critical value. Using a similar experimental set-up, Vigneau et al (2001) suggested that the thickness of the boundary layer does not have any significant influence on the dynamics of the cavity.…”
Section: Introductionmentioning
confidence: 99%